2021
DOI: 10.18187/pjsor.v17i1.2874
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Impact of Success Factors of Supply Chain Strategy and Flexibility on Supply Chain Performance

Abstract: Due to rapid globalization, an introduction of Goods and Services Taxes (GST), ban on BS-III vehicles, and rapid technological advancement creates new dimensions for the automobile industry in India especially for those who come in the category of small and medium enterprise (SMEs).In the current changing scenario victorious execution of supply chain management (SCM) practices can provide competitive leverage to Automobile manufacturers over their rivals particularly those who are poorly implemented supply cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…Therefore, the 3 rd hypothesis of the research was accepted. This result is in agreement with the findings of Vanichchinchai and Igel (2011), Masindet and Ogullah (2014), Kitheka (2015), Rajab (2015) Fouad et al (2015), Yu et al, (2019), Chandak et al, (2021), Alshibawi and Halleem (2022), Gonzalez et al, (2022), Jafari et al, (2022), Maaz and Ahmad (2022) and Zhang et al, (2022) who confirmed that customer focus influences the performance of the supply chain in manufacturing sector. According to the coefficient for the management commitment, the value of B is 0.489.…”
Section: H3: Customer Focus Impacts Supply Chain Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the 3 rd hypothesis of the research was accepted. This result is in agreement with the findings of Vanichchinchai and Igel (2011), Masindet and Ogullah (2014), Kitheka (2015), Rajab (2015) Fouad et al (2015), Yu et al, (2019), Chandak et al, (2021), Alshibawi and Halleem (2022), Gonzalez et al, (2022), Jafari et al, (2022), Maaz and Ahmad (2022) and Zhang et al, (2022) who confirmed that customer focus influences the performance of the supply chain in manufacturing sector. According to the coefficient for the management commitment, the value of B is 0.489.…”
Section: H3: Customer Focus Impacts Supply Chain Performancesupporting
confidence: 91%
“…Depending on what had been found by Yu et al, (2019), Chandak et al, (2021), Alshibawi and Halleem (2022), Gonzalez et al, (2022), Jafari et al, (2022), Maaz and Ahmad (2022) and Zhang et al, (2022), there is a significant impact of the customer focus and orientation on the performance of the supply chain. Therefore, the third hypothesis of the research was formulated as follows:…”
Section: 5supply Chain Performance and Customer Focusmentioning
confidence: 94%
“…SCF: According to Rajesh (2020), SCF is described as a company's ability to alter SC processes to increase performance in response to environmental changes; in addition, it allows a company to adapt to changes in an unpredictable environment and improve SCR to deal with fluctuating demand in market fluctuations. Five items adopted from the Chandak et al (2021) scale have been used to measure the SCF dimension (Table 3). Simatupang and Sridharan (2008), SCC is described as 'The process of independent firms (two or more organizations) working together throughout an SC to deliver products to end customers with the primary goal of maximizing long-term profit for all chain partners and achieving a competitive advantage'.…”
Section: Variables and Measuresmentioning
confidence: 99%
“…Strategi rantai pasok merupakan rangkaian keputusan yang dibuat oleh perusahaan untuk mengelola aktivitas pasokan dari bahan baku hingga produk jadi dengan tujuan meningkatkan kinerja dan keuntungan perusahaan (Chopra & Meindl, 2016). Strategi rantai pasok secara taktis diintegrasikan dalam jaringan rantai pasok perusahaan (Chandak et al, 2019). Oleh karena itu, strategi rantai pasok perlu terlebih dahulu ditetapkan sebelum desain yang lebih detail dirumuskan.…”
Section: Pendahuluanunclassified
“…Mengingat strategi rantai pasok merupakan penurunan dari strategi bersaing perusahaan (Chopra, 2019), maka keselarasan antara keduanya juga turut diperhatikan dalam penelitian ini. Strategi rantai pasok yang tepat harus sejalan dengan strategi bisnis/bersaing perusahaan (Chandak et al, 2019).…”
Section: Pendahuluanunclassified